Chronic radiation exposure as an ecological factor: Hypermethylation and genetic differentiation in irradiated Scots pine populations. (January 2018) - Volkova, P.Yu.; Geras'kin, S.A.; Horemans, N.; Makarenko, E.S.; Saenen, E.; Duarte, G.T.; Nauts, R.; Bondarenko, V.S.; Jacobs, G.; Voorspoels, S.; Kudin, M.
Abstract: Genetic and epigenetic changes were investigated in chronically irradiated Scots pine (Pinus sylvestris L.) populations from territories that were heavily contaminated by radionuclides as result of the Chernobyl Nuclear Power Plant accident. In comparison to the reference site, the genetic diversity revealed by electrophoretic mobility of AFLPs was found to be significantly higher at the radioactively contaminated areas. In addition, the genome of pine trees was significantly hypermethylated at 4 of the 7 affected sites. Graphical abstract: Highlights: Chronic radiation exposure changes the genetic structure of plant populations. Genomes of irradiated pines are hypermethylated. The level of hypermethylation does not depend on annual dose. Abstract : These results indicate that even relatively low levels of chronic radiation exposure can influence on the genetic characteristics and the methylation status of natural pine populations and that it should be considered as an important ecological factor reflecting the anthropogenic impact on ecosystems.